G138(P) Designing a Behavioural-Educational Intervention Using Intervention Mapping to Reduce the High Rates of Paediatric Asthma Hospital Admissions in an Inner-City Area of Birmingham. (4th June 2013) - Ikram, F; Cummins, C; Pattison, H; Barrett, L
Abstract : Aim: To develop asthma self-management programme working with children and families to prevent paediatric asthma emergency admissions in order to provide effective care and promote behaviour change (BC) towards effective management. Method: An evidence review on BC interventions for asthma was conducted; quantitative admissions data was collated; qualitative research was used to explore family and patient experiences. These were used in the six processes of intervention mapping: needs assessment, proximal programme objective matrices, theory-based methods and practical strategies, intervention design, adoption and implementation, and evaluation. Results: The six stages demonstrated that self-management behaviours are a critical component of asthma care and that childhood asthma care may be influenced through behaviour and environment. The process showed how intervention methods based on self-regulatory theory (Leventhal et al, 1984), behaviour change taxonomy (Michie & Abraham, 2008) and self-efficacy theory (Bandura, 1997) are applicable to self-management behaviours and can be translated into practical applications for asthma self-management. Step one involved conducting a literature review, collecting preliminary data and developing the asthma PRECEDE model. Step 2 highlighted the at-risk group and explores relevant theories/frameworks e.g. Asthma self-management behavioural framework (Bartholomew et al, 2001). Performance objectives and determinants were established in order to devise a change objective matrix. Step 3 linked BC techniques to determinants and change objectives in order to change behaviour. Step 4 was the intervention design targeting asthma self-management. Key features were child centred teaching including a video and facilitating family/GP links. Step 5 encompassed the logistics of the intervention i.e. delivery mode, costing and outcome expectations e.g. perceived benefits and better health. Step 6 outlined how the intervention would be evaluated including baseline and follow-ups, review of ED attendances, self-reported measures, Asthma Quality of Life Scales, Paediatric Asthma Control Test and Parental/Child Self-efficacy Scales. Conclusion: The intervention mapping process aided the design of an intervention tailored to the specific needs of a child/family. The intervention should help a child progress to more advanced asthma management and promote a tie between child/family and GP. Implementation and evaluation of this intervention in underway at Birmingham Children's Hospital to tackle the paediatric high rates of asthma hospital admissions.